Adsorption Studies of Chromium by Using Low Cost Adsorbents - Gandhi, N.; Sirisha, D.; Sekhar, K.B. Chandra (Our Nature, 2013)
The presence of toxic heavy metals such as chromium (VI) contaminants in aqueous streams, arising from the discharge of untreated metal containing effluents into water bodies, is one of the most important environmental problems. Adsorption is one of the effective techniques for chromium (VI) removal from wastewater. In the present study, adsorbent was prepared from low cost adsorbents and studies were carried out for chromium (VI) removal. Batch adsorption studies demonstrated that the adsorbents had significant capacity to adsorb the chromium from aqueous solution. It was found that the adsorption increased with increase in contact time and adsorbent dosage. An attempt was made to study mixed algae as an adsorbent for removal of chromium (VI). DOI: http://dx.doi.org/10.3126/on.v11i1.8238 Our Nature Vol.11(1) 2013: 11-16 ?